Chapter 1 Rethinking the Maria Luz Incident methodological cosmopolitanism and Meiji Japan - Mihalopoulos, Bill (Taylor & Francis, 2020)
This chapter adopts methodological cosmopolitanism to revisit the Maria Luz Incident (1872), a colourful diplomatic episode that involved two civil suits brought before a court created for the specific purpose of adjudicating whether the ship's captain ill-treated and abused his Chinese 'passengers' while the ship was anchored for repairs in Yokohama Port. The chapter argues that the Maria Luz Incident was not a seminal moment when rights talk was introduced to Japan. Rather, the incident was due to a lack of consensus in international law regarding whether the 'coolie trade' was free labour or slavery. The research traces how international law and narrow ideas of freedom (the freedom to enter contracts) became aligned with the workings of Japanese licensed prostitution.